Determination the Contamination Level of Mercury Due to Occupational Work - Raad A. Hamza; Amar Maula; Jarallah Muhsin; Talib M. Mahmoud (Journal of Madenat Alelem University College, 2013)
An investigation of mercury in blood and urine samples from 84 workers in two factories the first factory was Weaving Factory (which choose 38 worker) and the second factory was Paper Factory (which choose 46 worker) was carried out using non-inflammable atomic absorption technique revealed that the mercury levels were above that of the maximum permissible limit in the urine samples taken from eight out of 38 workers in the first factory and in three out of 46 workers in the second one. The mercury level in the blood samples from both factories within normal range (which is 50 microgram/L Hg in urine and 30 microgram/L Hg in blood). Clinical examinations of workers showed high level of mercury in their urine samples suggested same symptoms of toxicity with these elements.